(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2017)
Giant sialoliths are classified as those exceeding 15 mm in any one dimension.Sialolithiasis is the most common disease of salivary glands and approximately 80% of all reported cases of sialoliths occur in the sub mandibular salivary gland and its duct. A case of unusually large sialolith arising in the submandibular salivary gland duct presented which was removed surgically through per-oral approach.It was measured to be 38 mm along with its greatest length and 15 mm wide. JCMCTA 2016 ; 27 (2) : 81 - 83